Estimating Working Memory Capacity for Lists of Nonverbal Sounds - Li, Dawei (2013)
Working memory (WM) capacity limit has been extensively studied in the domains of visual and verbal stimuli. Previous studies have suggested a fixed WM capacity of typically about 3 or 4 items, based on the number of items in working memory reaching a plateau after several items as the set size increases. However, the fixed WM capacity estimate appears to rely on categorical information in the stimulus set (Olsson & Poom, 2005). We designed a series of experiments to investigate nonverbal auditory WM capacity and its dependence on categorical information. Experiments 1 and 2 used simple tones and revealed capacity limit of up to 2 tones following a 6-s retention interval. Importantly, performance was significantly higher at set sizes 2, 3, and 4 when the frequency difference between target and test tones was relatively large. In Experiment 3, we added categorical information to the simple tones, and the effect of tone change magnitude decreased. Maximal capacity for each individual was just over 3 sounds, in the range of typical visual procedures. We propose that two types of information, categorical and detailed acoustic information, are kept in WM, and that categorical information is critical for high WM performance.